Sentiments and emotions evoked by news headlines of coronavirus disease (COVID-19) outbreak - Aslam, Faheem; Awan, Tahir Mumtaz; Syed, Jabir Hussain; Kashif, Aisha; Parveen, Mahwish (Humanities & social sciences communications, 2020)
The chronic nature of coronavirus disease (COVID-19) outbreak and lack of success in treatment and cure is creating an environment that is crucial for mental wellbeing. Presently, we extracted and classified sentiments and emotions from 141,208 headlines of global English news sources regarding the coronavirus disease (COVID-19). The headlines considered were those carrying keyword coronavirus between the time frame 15 Janaury, 2020 to 3 June, 2020 from top rated 25 English news sources. The headlines were classified into positive, negative and neutral sentiments after the calculation of text unbounded polarity at the sentence level score and incorporating the valence shifters. In addition, the National Research Council Canada (NRC) Word-Emotion Lexicon was used to calculate the presence of eight emotions at their emotional weight. The results reveal that the news headlines had high emotional scores with a negative polarity. More precisely, around 52% of the news headlines evoked negative sentiments and only 30% evoked positive sentiments while 18% were neutral. Fear, trust, anticipation, sadness, and anger were the main emotions evoked by the news headlines. Overall, the findings of this study can be weaved together into important implications for emotional wellbeing and economic perspective.